Waktu Mitologis Dan Koeksistensi Narasi Dalam Memori Vulkanik Gunung Kelud Di Kediri - Salma Fauziah; A Zahid (Jurnal Ilmu Bahasa, Sastra, dan Budaya, 2026)
This studi examines how the concept of mythological time is interpreted and narrated by the community of Sugihwaras Village, Ngancar District, Kediri, which resides on the slopes of Mount Kelud, and how these mythological narratives coexist with scientific narratives in understanding volcanic eruption phenomena. Using a qualitative approach through ethnographic methods and in-depth interviews with six key informants including village officials, hamled heads, crater gatekeepers, community leaders, and disaster management authorities this study identifies three main findings. First, the Sugihwarsas community reconstructs volcanic time not throught  a linier-scientific chronology, but through thr rhythmic and cyclical Suro ritual calendar, in which eruption events are positioned as manifestation of cosmological relations between humans and the crater’s guardian entities. Second, scientific narratives (PVMBG, BPBD) and mythological narratives (Lembu Suro, Den Bagus Kliwon) do not negate one another but coexist functionally: scientific narratives govern emergency responses, while mythological narratives provide frameworks of meaning, psychological tranquility, and social cohesion. Third, the coexistence of both narratives plays a srategic role in forming and sustaining a collective disaster memory that has proven adaptive, as evidenced by the zero-victim outcome of the 2014 eruption.This study contributes to the fields of  disaster ecology and memory anthropology by proposing the concept of adaptive coexistence as a new analytical framework.